Evaluation of Labrador Sea Water formation in a global Finite‐Element Sea‐Ice Ocean Model setup, based on a comparison with observational data. Issue 3 (7th March 2014) - Scholz, P.; Kieke, D.; Lohmann, G.; Ionita, M.; Rhein, M.
Abstract The deep water formation in the Labrador Sea is simulated with the Finite‐Element Sea‐Ice Ocean Model (FESOM) in a regionally focused, but globally covered model setup. The model has a regional resolution of up to 7 km, and the simulations cover the time period 1958–2009. We evaluate the capability of the model setup to reproduce a realistic deep water formation in the Labrador Sea. Two classes of modeled Labrador Sea Water (LSW), the lighter upper LSW (uLSW) and the denser deep LSW (dLSW), are analyzed. Their layer thicknesses are compared to uLSW and dLSW layer thicknesses derived from observations in the formation region for the time interval 1988–2009. The results indicate a suitable agreement between the modeled and observational derived uLSW and dLSW layer thicknesses except for the period 2003–2007 where deviations in the modeled and observational derived layer thicknesses could be linked to discrepancies in the atmospheric forcing of the model. It is shown that the model is able to reproduce four phases in the temporal evolution of the potential density, temperature, and salinity, since the late 1980s, which are known in observational data. These four phases are characterized by a significantly different LSW formation. The first phase from 1988 to 1990 is characterized in the model by a fast increase in the convection depth of up to 2000 m, accompanied by an increased spring production of deep Labrador Sea Water (dLSW). In the second phase (1991–1994), the dLSW layer thickness remains on a high level for several years, while the third phase (1995–1998) features a gradual decrease in the deep ventilation and the renewal of the deep ocean layers. The fourth phase from 1999 to 2009 is characterized by a slowly continuing decrease of the dLSW layer thickness on a deeper depth level. By applying a composite map analysis between an index of dLSW and sea level pressure over the entire simulation period from 1958 to 2009, it is shown that a pattern which resembles the structure of the North Atlantic Oscillation (NAO) is one of the main triggers for the variability of LSW formation. Our model results indicate that the process of dLSW formation can act as a low‐pass filter to the atmospheric forcing, so that only persistent NAO events have an effect, whether uLSW or dLSW is formed. Based on composite maps of the thermal and haline contributions to the surface density flux we can demonstrate that the central Labrador Sea in the model is dominated by the thermal contributions of the surface density flux, while the haline contributions are stronger over the branch of the Labrador Sea boundary current system (LSBCS), where they are dominated by the haline contributions of sea ice melting and formation. Our model results feature a shielding of the central Labrador Sea from the haline contributions by the LSBCS, which only allows a minor haline interaction with the central Labrador Sea by lateral mixing. Based on the comparison of the simulated and measured LSW layer thicknesses as well as vertical profiles of potential density, temperature, and salinity it is shown that the FESOM model is a suitable tool to study the regional dynamics of LSW formation and its impact on a global, not regional restricted, scale.